INTEGRATION OF DIGITAL TECHNOLOGY IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) REALIZATION OF SMART CITY (CASE STUDY OF MEDAN DENAI DISTRICT) - Muhammad Naufal Rahadian; Tengku Irmayani; Nurman Achmad (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the integration of digital technology in Micro, Small, and Medium Enterprises (MSMEs) in Medan Denai District within the framework of smart city development. The research focuses on identifying the patterns of digital platform adoption, the challenges faced by MSME actors, and the implications for local economic transformation. A qualitative descriptive approach was employed, using in-depth interviews, observations, and documentation involving MSME actors, local government representatives, and related stakeholders. The findings reveal that digital platform adoption among MSMEs is primarily concentrated on marketing activities through social media and online marketplaces, while the use of digital technology for financial management, inventory control, and data-driven decision-making remains limited. Constraints such as low digital literacy, limited access to continuous training, and insufficient institutional support hinder deeper digital integration. Although basic digital infrastructure is available, its utilization has not been optimized to support MSME productivity and competitiveness. The study concludes that smart city implementation in Medan Denai has not yet fully empowered MSMEs as key actors in the digital economy. Therefore, a more inclusive and MSME-centered smart city strategy is required, emphasizing sustained capacity building, integrated digital systems, and cross-sector collaboration to strengthen local economic resilience.